A microcosm study of microbial community profiles during sediment remediation using pyrolyzed oyster shells. (15th August 2022) - Patil, Maheshkumar Prakash; Woo, Hee-Eun; Lee, In-Cheol; Nakashita, Shinya; Kim, Kyeongmin; Kim, Jong-Oh; Kim, Kyunghoi
Abstract: The accumulation of organic and inorganic components in sediments leads to a deterioration in the environment and an imbalance in the coastal ecosystem. Currently, capping is the most effective technology for remediating polluted sediment and restoring ecosystems. A microcosm experiment was designed using pyrolyzed oyster shell (POS). These were mixed in with coastal sediment or added as a capping layer. The results showed that POS effectively decreased pollutants, including PO4 –P and NH4 –N. Metagenomics analysis was performed using 16S rRNA gene sequencing and the most abundant phyla identified in the POS treated and untreated sediments were Proteobacteria, followed by Firmicutes, Bacteroidetes, Chloroflexi, Fusobacteria, Nitrospirae, and Spirochaetes. The relative abundance of Proteobacteria members of the Class Gammaproteobacteria significantly increased, but Deltaproteobacteria gradually decreased throughout the experiment in POS-covered sediment. This suggests that the POS effectively promoted a shift from anaerobic to facultative anaerobic or aerobic microbial communities in the sediment. Dominant species of facultative anaerobic or microaerophilic bacteria from the order Chromatiales and phylum Nitrospirae were observed in the POS-covered sediment. Based on these study results, it can be concluded that POS is an effective covering material for sediment remediation and restores the microbial communities in sediments. Graphical abstract: Image 1 Highlights: Pyrolyzed oyster shell capping is an effective technique for sediment remediation. Pyrolyzed oyster shell capping effectively controlling phosphate release, and reducing nitrogen. Capping enhanced microbial population, which helps to reduce organic matter in low-oxygen environments. Microbial communities undergo anaerobic to aerobic or facultative anaerobic transformations.